please simplify this equation

wonderwoman

New member
Joined
Jan 30, 2014
Messages
1
if K^(x-1) = n+d/Zx, tell me how you get to the below step from this first step.

K = (Zx/n+d)^1/(1-X)

Thanks in advance.
 
Protocol

if K^(x-1) = n+d/Zx, tell me how you get to the below step from this first step.

K = (Zx/n+d)^1/(1-X)

Thanks in advance.

We help you to help yourself. What we need is to see your work in progress. What have you tried, where are you stuck, what type of equation is it you are trying to solve?
 
Top